Advances in fuzzy object-oriented databases modeling and applications - Ma, Zongmin, 1965- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
Collecting the latest research results from the leading researchers in the field of fuzzy object-oriented databases, Advances in Fuzzy Object-Oriented Databases: Modeling and Applications provide a single source for current research and practical applications in fuzzy object-oriented databases. This book includes major aspects of fuzzy object-oriented database modeling - conceptual, logical and physical, as well as details of implementations and applications. Readers will benefit from a complete understanding of the notions, techniques, and methods related to the research and developments of fuzzy object-oriented databases. This book can act as a starting point and a reference for their research and developments and stimulate the interest in the field of fuzzy object-oriented databases and further promote the research in the field.